An environmental benefits and costs assessment model for remanufacturing process under quality uncertainty. (20th March 2018) - Liao, Haolan; Deng, Qianwang; Wang, Yuanrui; Guo, Shumin; Ren, Qinghua
Abstract: Recycling and remanufacturing of end-of-life products are value-added processes and have great environmental benefits. Although comparative analyses of manufacturing and remanufacturing of these products are common, only a few are based on a quantitative model that comprehensively evaluates the environmental benefits of remanufacturing under quality uncertainty and explore how the environmental benefits will be affected by the fluctuations in the quality coefficient. This study has developed a complex quality coefficient measurement method to describe the quality uncertainty in returned items. Followed by real-life data analysis and validated by numerical experiments, this study comparatively analyzes the carbon emissions between whole machine remanufacturing and cannibalization and between component remanufacturing and recycling. It also investigates the internal relationship between the quality condition and environmental benefits of the remanufacturing system. The results show that the reductions in carbon emissions increase with rising complex quality coefficient but its marginal increase rate decreases rapidly. The model provides a guideline for the government to implement environmental regulations and a reference for firms to effectively fulfill their environmental responsibility. Highlights: Set up a model on environmental advantage of remanufacture over manufacture. Design an algorithm for quality coefficient to quantify the uncertainty in returns. Establish the relation between environmental benefits and quality coefficient. Derive the optimum solution to quality coefficient in acquisition of EOL items.